Lower Bound for E Capacity of Discrete Memoryless Channel with Two-Sided State Information - Haroutunian, Mariam E.; Muradyan, Arthur R. (Mathematical Problems of Computer Science, 2021)
We study the channel with two-sided state information, a discrete memoryless channel with finite input and output alphabets and random state sequence. Partial information about the state sequence is available to the encoder and decoder. Applications of this study include watermarking, data hiding, communication in presence of partially known interferers. The capacity of this model was obtained by Cover and Chiang in [1]. In this paper the random coding bound of E-capacity is derived for considered model which can be called also generalized channel with state information, as it includes four possible situations of the channel with random parameter.